Management Of Assembly Taklim Al-Hikmah Management In Increasing Residents' Interest In Following Resurrections In Kebun Bunga Village, Sukarami Sub-District, Palembang City - Alrama Tripina Anamiah; Nuraida Nuraida; Anang Walian (CV. Ulil Albab Corp, 2023)
The thesis entitled